Metode Konstruksi Jetty Untuk Melindungi Muara Sungai, Studi Kasus Sungai Bogowonto - Pranu Arisanto; Maulida Rahma; Elia Salsabila Yasminasarie (Universitas Batanghari Jambi, 2023)
The location estuary of the Bogowonto river is very strategic because it is on the west side of YIA airport (Yogyakarta International Airport). The condition of the Bogowonto river will directly affect the airport, especially related to flood conditions. The construction of an estuary is necessary to maintain sediment transport so that sediment buildup does not occur flooding. One of the constructions at the estuary to prevent this is the construction of a jetty. The use of jetty constituent elements can withstand seawater abrasion. Concrete is an alternative that is used with the consideration that it can control the shape, compressive strength, and weight. The elements that make up this jetty are in the form of blocks and tetrapods with a certain weight. The research was carried out by analyzing the work of tetrapod concrete as a constituent of jetty construction. Limited workplace conditions for storage and production require a proper cycle from production and storage to installation. The research was conducted by direct observation in the field and interviews with the work executors. The results of field observations obtained work methods carried out by executors by circulating concrete production with two methods, namely concrete with the addition of addictive materials and without the addition of additives. This additional material accelerates the concrete's initial compressive strength so that the concrete mold can be immediately opened and used again.